In a world process. The beginnings of the tourist activity in Peru (1800-1850) - Armas Asín, Fernando (2016)
The article investigates the origins of tourism in Peru during the first half of the nineteenth century, in acontext of arrival of an increasing number of foreign travelers as well as interest on the Peru that arousevarious publications in Europe. Following a series of stories of travelers, it establishes the places of attractionfor foreign visitors and what was the situation of the lodges, roads as well as the food that were accessible. Itargues that the situation of this embryonic tourism was the same that existed in Europe before the emergenceof the consumer society and mass.